A gendered perspective of post-apartheid political killings: a case study of uMzimkhulu, Kwa-Zulu Natal - Ngqwala, Namhla (My University, 2021)
This study uses a gendered perspective to explore political killings in post-apartheid South Africa. It uses the uMzimkhulu municipality area of Harry Gwala district in the province of Kwa Zulu Natal (KZN) as its case study. A gendered analysis of political violence, focused specifically on women in this case, is important to explore if we are to better understand how patriarchy and hegemonic masculinities contribute to political killings within local government. The gendered motive appears when perpetrators preserve hegemonic men's control of politics. Moreover, political violence can be gendered especially when men use coercion, intimidation, and ultimately violence to maintain the status quo of masculine hegemonic political dominance. Both men and women experience violence that is specifically designed to deter their involvement and participation in politics. However, women who participate in politics are confronted by an intersection of their cultural, political, and social environment that becomes unfavourable due to the violence of political killings. In this study, attention is drawn to the region's threat, intimidation, and killing of politicians and councillors. The study also focuses attention on enhancing theoretical specificity on how political violence is gendered and explores the perspective of political killing at the local level. This research uses exploratory qualitative research methods to gain an understanding of the underlying reasons for the political killings in uMzimkhulu
A mini- dissertation presented in partial fulfilment for the degree of Master of Arts in Political Studies to the Faculty of Humanities at the University of the Witwatersrand, 2021